Neoplasias na Infância - Serapião, Carlos José (2023)
The awareness of the interst in malignancy during the childhood became obvious throug statistical reporting from various sources, showing that the mortality due to câncer in children under the age of 15 years is second only to accidents. The types of tumors and their behavior differ from the adult and some of them do not have counterpart in this age group. Peculiarities in the distribution of childhood cancer suggest the existence of important factors for the etiopathogenic hypothesis, and the relationship with mal-formations seems to be a remarkable finding. The categorization of the tumor is based on morphological and histogenetic characteristics, as well as the age of incidence. The main group is represented by dysontogenetic tumor, wich are originating in faulty embriogenesis. Other group of tumor developing in heterotopias, developmental vestiges, and other developmental defects. Juvenil tumor and adult-type tumors, are related with the age group, althoug are not limited to the pediatric age.